Platelet reactivity after clopidogrel loading in patients with acute ischemic stroke - Enomoto, Yukiko; Shoda, Kenji; Mizutani, Daisuke; Matsubara, Hirofumi; Egashira, Yusuke; Iwama, Toru (Frontiers in Neurology, 2022)
Objective It remains unclear when sufficient antiplatelet effect is achieved after administration of a loading dose of clopidogrel in patients with acute ischemic stroke (AIS). This study aimed to evaluate the clopidogrel response in patients with AIS identified by the platelet function test (PFT). Methods P2Y12 reaction unit (PRU) values measured using VerifyNow at baseline and at 6, 24, and 72 h after administration of a loading dose (300 mg) of clopidogrel were compared between patients with AIS and those of other cerebrovascular diseases (CVD). The prevalence of clopidogrel abnormal response and its associated factors were examined. Results The PRU value was significantly reduced with time in the other CVD group (p < 0.0001), and also in the AIS group (p = 0.0073). The PRU values were significantly higher in the AIS group than in the other CVD group (p < 0.0001 between the groups, baseline: 314 ± 53 vs. 284 ± 62, p = 0.35; 6 h: 290 ± 66 vs. 214 ± 71, p = 0.016; 24 h: 270 ± 75 vs. 190 ± 70, p < 0.0001; and 72 h: 231 ± 76 vs. 163 ± 93, p = 0.105). The prevalence of clopidogrel hypo-responder (PRU > 240 at 24 h after administration) was higher in the AIS group (79 vs. 33%, p < 0.0001) and associated with the baseline PRU value but not with the cytochrome P450 2C19 genotype or clinical ischemic events. Conclusions Residual platelet reactivity at 24 h after clopidogrel loading was substantially higher in patients with AIS than in patients with other CVD. In addition, most patients with AIS were judged to be hypo-responders on PFT. This should be carefully interpreted in patients with AIS because of poor specificity for predicting clinical ischemic events.